Applying urban morphology theory to design practice. Issue 2 (3rd March 2016) - Sanders, Paul; Baker, Douglas
Abstract: The aim of this paper is to investigate the relationship between research and design through an applied example of how architects can approach the design for a building guided by data derived from morphological research. An Expert Focus Group consisting of nine leading architects and urban designers from Brisbane, Australia, was given the task of testing this proposition. Analysis of the workshop outcomes are examined, and the design drawings of each participant are assessed to determine the relative congruence of the design proposals within the morphological commodity of the specific context. In addition, qualitative data, captured through verbal and written feedback is assessed highlighting the participants' observations and experiences of the workshop. This paper makes a contribution to the current debate within the field on the opportunities of integrating research with practice.